Three-Dimensional Printed Model and Virtual Reconstruction: An Extra Tool for Pediatric Solid Tumors Surgery - Ángela Sánchez-Sánchez; Óscar Girón-Vallejo; Ramón Ruiz-Pruneda; Maria Fernandez-Ibieta; Darío García-Calderon; Vanesa Villamil; María Cristina Giménez-Aleixandre; Carlos Andrés Montoya-Rangel; Juan Pedro Hernández Bermejo (Georg Thieme Verlag KG, 2018)
Abstract Introduction Three-dimensional (3D) technology is increasingly applied for planning challenging surgical interventions. We report our experience using 3D printing and virtual reconstruction for surgical planning of complex tumor resections in children. Methods Data were obtained from preoperative magnetic resonance. imaging analysis and 3D virtual recreations were performed using specialized computer software. 3D real-scale geometry models, including tumor, adjacent organs, and relevant vascularization, were printed in colorimetric scale and different materials for optimal structures discrimination. Results Four complex cases were selected. The first case was a bilateral Wilms tumor. The volumetric reconstruction proved the presence of enough healthy renal tissue, allowing bilateral nephron-sparing surgery. In the second case, reconstruction contributed to the location of pulmonary metastases. The third case was an abdominal neuroblastoma stage L2. The 3D model was of high value for planning and as a reference during the intervention. The last case is a cervico-thoracic neuroblastoma with an anatomopathological diagnosis of ganglioneuroma, located at the cervico-mediastinal juncture, in close relationship with the cervical vessels. Conclusions 3D reconstruction and the full-scale printing models are a useful tool in cases of complex tumor resections as they contribute to a better understanding of the relationships between the tumor and adjacent organs, helping to anticipate certain surgical complications. They also provide additional information to conventional imaging tests, being able to influence therapeutic decisions and facilitate the understanding by the family, improving doctor-patient communication.